EXCLUSIVE BREASTFEEDING AND COMPLEMENTARY FEEDING DIVERSITY AS DETERMINANTS OF STUNTING AMONG CHILDREN AGED 6-24 MONTHS IN A LOCAL HEALTH CENTRE AREA OF BERAU, EAST KALIMANTAN, INDONESIA - Ratih Wirapuspita Wisnuwardani; Ismail Kamba; Nurul Afiah; Reny Noviasty; Winny Yolanda; Wanzahun Godana Boynito (The Indonesian Journal of Public Health, 2026)
Introduction: Stunting is a critical issue in Indonesia, particularly in Berau, East Kalimantan, where 28.6% of children at Gunung Tabur Health Center were stunted in 2021. Factors contributing to stunting include complementary feeding practices and exclusive breastfeeding, which play an important role. Aims: The study examined the correlation between the prevalence of stunting at the Gunung Tabur Health Center in East Kalimantan and feeding practices, namely exclusive breastfeeding and the use of diverse supplemental foods. Methods: This research used a case-control design, conducted in August-December 2022, and involved 66 moms of infants aged 6 to 24 months in the working area of the Gunung Tabur Health Center, Berau Regency, East Kalimantan. Data were collected using a questionnaire on exclusive breastfeeding and the diversity of complementary foods. For statistical analysis, chi-square analysis was employed. Results: In the initial six months of existence, infants who weren’t exclusively breastfed faced a heightened risk of stunting, whereas 86.4% of exclusively breastfed newborns were unaffected by growth failure. Stunting and exclusive breastfeeding are significantly correlated (p = 0.001). Furthermore, a lack of variety in complementary foods was correlated with growth retardation (p = 0.008), with 90.9% of infants fed a limited range of complementary foods showing growth retardation. Conclusion: The findings indicate a substantial association between exclusive breastfeeding, diverse supplemental foods, and the prevalence of stunting in the operational region of East Kalimantan’s Gunung Tabur Health Center in 2022.